PROSTAGLANDIN F2α ADMINISTRATION ON DAY 8 POSTPARTUM LEADS TO EARLY RESUMPTION OF OVARIAN CYCLIC ACTIVITY IN DAIRY CATTLE - SHARMA, A; SINGH, M; SHARMA, A; KUMAR, P (The Indian Journal of Animal Reproduction, 2022)
Dairy cattle assigned to four treatment groups were administered PGF2α analogue (cloprostenol) on day 8 or day 25 postpartum (n=6 each), or antibiotic from day 1 to 5 postpartum (n=6), or kept as untreated control (n=5). The monitoring of uterine involution of previous gravid and non-gravid uterine horn, and first postpartum ovulatory follicle (OF) and subsequent corpus luteum (CL) was performed by transrectal ultrasound scanning at weekly interval. The appearance of OF and subsequent CL was early (16.17±2.81 and 23.16±2.81 d, respectively; p<0.05) in dairy cattle administered PGF2α on day 8 postpartum as compared to other groups. In brief, PGF2α administration on day 8 postpartum can lead to early resumption of ovarian cyclic activity in dairy cattle.